2023
DOI: 10.1038/s41467-023-40726-8
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of marine bacteria of the SAR202 clade

Yeonjung Lim,
Ji-Hui Seo,
Stephen J. Giovannoni
et al.

Abstract: Bacteria of the SAR202 clade, within the phylum Chloroflexota, are ubiquitously distributed in the ocean but have not yet been cultivated in the lab. It has been proposed that ancient expansions of catabolic enzyme paralogs broadened the spectrum of organic compounds that SAR202 bacteria could oxidize, leading to transformations of the Earth’s carbon cycle. Here, we report the successful cultivation of SAR202 bacteria from surface seawater using dilution-to-extinction culturing. The growth of these strains is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…7 ) 34,35 . Within the Chloroflexota class Dehalococcoidia , the model correctly identified the order Dehalococcoidales to be entirely anaerobic and orders Tepidiformales /OLB14 and SAR202/UBA1151 as containing aerobes, in agreement with previous reports 3638 . Elevated optimal temperature was correctly predicted for phyla Hadarchaeota and Calescibacterota ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…7 ) 34,35 . Within the Chloroflexota class Dehalococcoidia , the model correctly identified the order Dehalococcoidales to be entirely anaerobic and orders Tepidiformales /OLB14 and SAR202/UBA1151 as containing aerobes, in agreement with previous reports 3638 . Elevated optimal temperature was correctly predicted for phyla Hadarchaeota and Calescibacterota ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Nonetheless, the powerful oxidative enzymes (e.g., FMNOs) that are encoded by deep-sea lineages of the SAR202 clade are also present in the surface subgroups in fewer copies ( Landry et al, 2017 ; Saw et al, 2020 ). Recently, several closely related strains of SAR202 bacteria in subgroup Ia were successfully cultivated ( Lim et al, 2023 ). Subsequent growth experiments showed that the subgroup Ia SAR202 did not reach the exponential phase until 50 days at 20°C and the growth responses to fucose and rhamnose were slow and did not reach the highest cell density until the late exponential phase, which coincided with our detection of increased SAR202 abundance in the treatment on day 60 ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that SAR202 bacteria are specifically utilizing a unique niche of high-abundance unsaturated compounds that were either not consumed by other bacteria or produced by bacteria in phase 1. It has been postulated that SAR202 bacteria are capable of exploiting the DOM that other deep-sea bacterioplankton cannot degrade ( Varela et al, 2008 ; Lim et al, 2023 ). Through the ultrahigh-resolution FT-ICR-MS approach, our data provided first-hand evidence that the SAR202-MFs possess possibly aromatic but certainly unsaturated characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…This metabolic fate is also hydrolyzed to pyruvate and l -lactate by the hydrolase (LRA6), which is phylogenetically close to FucG. Recently, non-phosphorylating l -fucose and/or l -rhamnose pathway(s) were shown to play important physiological roles in the gastrointestinal pathogen Campylobacter jejuni 6 and (previously unculturable) marine bacteria of the SAR202 clade 7 .…”
Section: Introductionmentioning
confidence: 99%